Modeling of Stress-Strain Relationship for Fibrous Concrete Under Cyclic Loads - Bayar J. Al-Sulayfani; Hatim T. Al-Taee (Engineering and Technology Journal, 2008)
A mathematical model to predict the stress–strain behavior of fibrous concrete compositesunder random cyclic compressive loadings is developed. The envelopeunloading strain is used as an index of load history, while the plastic strain andreloading strain are predicted as functions of the envelope unloading strain for bothfull and partial unloading and reloading. The model is independent of the expressionused for the envelope curve. Comparison with cyclic data shows good agreement.The model can be used for completely random loadings, in both the pre–peak andpost–peak ranges. It is suitable for both plain and fibrous concrete composites. Themodel has been built using MATLAB language computer program facilitating theadvanced mathematicaldifficulties of solving and differentiating complex expressions.In this paper, the monotonic stress–strain curves of Al-Sulayfani model [1] for fibrousconcrete had been adopted.